Have you eaten yet? : stories from Chinese restaurants around the world - Kwan, Cheuk (Pegasus Books, 2023)
"An eye-opening and soul-nourishing journey through Chinese food around the world. From Cape Town, South Africa, to small-town Saskatchewan, family-run Chinese restaurants are global icons of immigration, community and delicious food. The cultural outposts of far-flung settlers, bringers of dim sum, Peking duck and creative culinary hybrids, Chinese restaurants are a microcosm of greater social forces. They are an insight into time, history, and place. Author and film-maker Cheuk Kwan, a self-described "card-carrying member of the Chinese diaspora," weaves a global narrative by linking the myriad personal stories of chefs, entrepreneurs, labourers and dreamers who populate Chinese kitchens worldwide. Behind these kitchen doors lies an intriguing paradox which characterizes many of these communities: how Chinese immigrants have resisted--or have often been prevented from--complete assimilation into the social fabric of their new homes. In both instances, the engine of their economic survival--the Chinese restaurant and its food--has become seamlessly woven into towns and cities all around the world. An intrepid travelogue of grand vistas, adventure and serendipity, Have You Eaten Yet? charts a living atlas of global migration, ultimately revealing how an excellent meal always tells an even better story"--